A pilot study to assess the feasibility and uptake of MindDEC, a mindfulness-based self-management course for type 2 diabetes - P.S. Deo; T.M. Barber; C. Gotts; M. Villarreal; H. Randeva; S. Brown; J. Bath; P. O'Hare; S. Chaggar; P. Hanson (Elsevier, 2024)
Objective: The study aimed to investigate the feasibility of a remote mindfulness based self-management intervention for individuals with type 2 diabetes. It is important to further our understanding of how to improve self-management to improve health outcomes and low levels of uptake to self-management courses. Method: 29 participants with type 2 diabetes were recruited from the University Hospital Coventry and Warwickshire NHS trust. Three groups of participants engaged with a remote mindfulness based self-management intervention, which were delivered sequentially. After each intervention was complete, patient feedback was retrieved and implemented into the following intervention. The quantitative analysis comprised of descriptive statistics, independent sample t-test, paired sample t-test and multiple regression analysis. A qualitative analysis was also conducted through reflexive thematic analysis (RTA) to understand participant's perspective on the intervention. Results: There was a total of 17 who attended the course (59 %) and a total drop out of 12 participants over the three courses (41 %). The qualitative findings reported three main themes: (1) Eating to manage my emotions rather than my diabetes (2) Implementing mindfulness has helped me manage my emotions (3) Medication rather than self-management behaviours control my diabetes. The focus group feedback included participants' appreciation of the community aspect of the intervention and their perception that the current course was more interactive compared to previous interventions. In addition, participants highlighted the importance of offering the course at an earlier stage of diagnosis to provide further support at the beginning of their diabetes journey. No significant findings were reported for the independent sample t-test, paired sample t-test and multiple regression analysis. Conclusion: The qualitative findings suggested that the course was beneficial, especially in demonstrating how mindfulness could aid self-management for individuals living with type 2 diabetes. Further funding and trials are warranted to improve the quality of technology used and to assess impact on diabetes control and mental health.